The Non-Evaginated Secondary Prosencephalon of Vertebrates - Moreno, Nerea; González, Agustín (Frontiers in Neuroanatomy, 2011)
The secondary prosencephalon (telencephalon plus hypothalamus) is probably the most complex area of the brain, with complicated patterning specifications. As yet, no prosomeric subdivisions have been reported and only distinct histogenetic territories have been recognized. In the present comparative study we analyzed cross-correlated expression maps in the non-evaginated territories of the secondary prosencephalon in different vertebrates throughout development, to assess the existence of comparable divisions and subdivisions in the different groups. Each division is characterized by expression of a unique combination of developmental regulatory genes, and each appears to represent a self-regulated and topologically constant histogenetic brain compartment that gives rise to a specific cell group. The non-evaginated area of the telencephalon corresponds to the preoptic region, whereas the hypothalamus, topologically rostral to the diencephalic prethalamus, includes basal (mammillary and tuberal) and alar (paraventricular and suprachiasmatic) parts. This complex area is specified by a cascade of transcription factors, among which the Dlx family members and Nkx2.1 are essential for the correct development. The only exception is found in the subdivision named termed the supraoptoparaventricular area, in which the transcription factor Orthopedia is essential in restricting the fate of multiple categories of neuroendocrine neurons, in the absence of the Dlx/Nkx2.1 combination. Our analysis, based on own data and published results by other researchers, suggests that common features are shared at least by all tetrapods and, therefore, they most likely were present in the stem tetrapods. The available data for agnathans (lampreys) and other fish groups indicate that not all subdivisions of the secondary prosencephalon were present at the origin of vertebrates, raising important questions about their evolution.